Upaya Mitigasi Risiko Pembiayaan pada BMT Assyafiiyah Berkah Nasional Pekalongan - Erika Septi Triviana; Esty Apridasari; Thoyyibatun Nisa; Witantri Dwi Swandini (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The surge in Non-Performing Financing (NPF) from 1.89% to 8.75% in 2025 indicates the need for a more effective risk mitigation strategy at KSPPS BMT Assyafiiyah BN Pekalongan. This study uses a qualitative approach to analyze the effectiveness of preventive, detective, and curative risk mitigation. The findings show that although the 5C+1S procedure as well as the financing restructuring have been implemented, the effectiveness of mitigation remains low. This is due to the high subjectivity of analysis due to the social closeness between managers and members, as well as a monitoring system that is still manual so that early detection of late payment failures is carried out. These conditions contribute to increasing NPFs and lowering institutional liquidity stability. The research recommends the implementation of the digitization of an objective data-based early warning system as well as the standardization of financing feasibility assessments to reduce the risk of default. Thus, digital transformation in risk mitigation is expected to be able to maintain operational sustainability and increase members' trust in the institution.